Reviews and Practice of College Students Regarding Access to Scientific Knowledge: A Case Study in Two Spanish Universities - Sáez López, José Manuel; Ruiz Ruiz, Jose María; Cacheiro González, Maria-Luz (International Review of Research in Open and Distributed Learning, 2013)
This study analyzes the concepts, attitudes, and practices of 327 pedagogy students from two major Spanish universities related to the process of finding academic information utilizing open access. A training program has been developed through an innovation project (PIMCD) to address the problem of the lack of university training designed to enable students to access reliable sources of scientific knowledge. A mixed questionnaire with a pretest-posttest design, applying a descriptive analysis, a factor analysis, and a Wilcoxon test was administered to students. The results show that it is essential to provide information and training to encourage university students to learn how to find and manage rigorous and reliable sources of information. While searching for academic information, Spanish students tend to focus on the use of Google and, to a lesser extent, Google Scholar. Although there are no significant limitations of access to Spanish language articles, students’ attitudes remain very positive towards the concept of open access. In short, in accordance with the study results, the promotion of educational activities relating to the search for and selection of information and the use of reliable and rigorous academic content is highly recommended in the university context.